Atribuição de gravidade à deficiência física em função da extensão do acometimento e do contexto escolar - Araújo, Rita De Cássia Tibério [UNESP]; Omote, Sadao [UNESP] (Associação Brasileira de Pesquisadores em Educação Especial - ABPEE, 2005)
The perception people have about injury level of a disability is an important variable to be considered in the inclusion. This study aimed to identify the variation in the attribution of mild or severe injury to physical handicap depending upon four information sets. Ninety-seven Pedagogy students took part in the study. Data collecting instrument, consisting of a descriptive text concerning the need of computer keyboard adaptation for reading and written activity accomplishment by a hypothetical student, took account of two body conditions of motor deficit and two teaching settings. The indication of upper limb movement limitation characterized the partial injury. The global injury was represented by the indication of both upper limbs and lower ones movement limitation, besides difficulty in balance maintenance in seated position. The teaching settings were informed pointing out the use of adapted resource in regular class or in special class. Combining these indications, four conditions, whose effects on seriousness level attribution to the motor injury, were constituted. The four conditions received growing attribution of severe motor injury in following order: using adapted resource in regular class and partial injury, using adapted resource in regular class and global injury, using adapted resource in special class and partial injury and using adapted resource in special class and global injury. The results showed that the segregated teaching setting and global injury information tended toward maximization of the idea of injury severity.

A percepção que as pessoas têm da gravidade da deficiência é uma variável relevante a ser considerada na perspectiva da inclusão.Este estudo objetivou identificar a variação na atribuição de grau leve ou severo à deficiência física dependendo de quatro conjuntos de informações. Participaram do estudo 97 estudantes de um Curso de Pedagogia. O instrumento de coleta de dados, estruturado com base em texto descritivo acerca da necessidade de adaptação do teclado de computador para a realização da atividade de leitura e escrita por um aluno hipotético, contemplou duas possibilidades de extensão corporal de déficit motor e duas possibilidades de modalidade de ensino. A indicação da limitação de movimentos dos membros superiores caracterizou o acometimento parcial e a dos membros superiores e inferiores, além de dificuldade para manutenção do equilíbrio na posição sentada, representou o acometimento global. As modalidades de ensino foram informadas pela indicação do uso de recurso em classe comum e do uso de recurso em classe especial. Combinadas duas a duas, essas indicações compuseram quatro condições, cujos efeitos sobre a atribuição de gravidade ao acometimento motor foram analisados. As quatro condições receberam atribuição crescente de grau severo de acometimento motor e, conseqüentemente, atribuição decrescente de grau leve, na seguinte ordem: uso do recurso em classe comum e acometimento parcial, uso do recurso adaptado em classe comum e acometimento global, uso do recurso em classe especial e acometimento parcial e uso do recurso em classe especial e acometimento global. Os resultados demonstraram que a situação segregada de ensino e a informação sobre acometimento global tenderam a exacerbar a idéia de severidade da deficiência.
Attribution of seriousness degree to physical handicap due to injury extension and school setting
Keywords: special education; physical handicap; disability seriousness; educação especial; deficiência física; gravidade da deficiência